Effectiveness of online caries management platform in children's caries prevention: A randomized controlled trial - Siqi Yan; Song Luo; Xiaoxia Yang; Lidan He; Xinyi Chen; Guoying Que (Frontiers Media S.A., 2023)
PurposeTo construct an online caries management platform and evaluate its efficacy in children's caries prevention based on caries risk.MethodsThe study participants were second-grade pupils. The caries risk assessment tool (CAT) was used to grade caries risk for all participants, who were randomly divided into the experimental (114 pupils) and control (111 pupils) groups. The experimental group used the Internet for caries management, while the control group was managed by traditional lecturing in classroom. The caries status of each surface of the first permanent molars was recorded. The basic information and oral health knowledge, attitude, and behaviors of participants were collected by questionnaire. One year later, outcome data were collected. Pearson's chi-squared test was used to analyze the caries risk assessment items and oral health behaviors. The Mann-Whitney U-test was used to analyze the decayed-missing-filled surfaces (DMFS) index, plaque index, and scores of oral health knowledge and attitude. P < 0.05 was considered statistically significant. This study was available on the website of Chinese Clinical Trials Register (No: MR-44-22-012947).ResultsAfter 1 year, the oral health knowledge score was improved by 20.58% (P < 0.001) in the experimental group and 6.02% in the control group. The plaque index was improved by 49.60% (P < 0.001) in the experimental group and 21.01% in the control group. The DMFS index increased in both groups but there were no significant differences (P = 0.608). The experimental group had a better improvement effect in caries risk assessment items than the control group, including "whether the frequency of eating sugary snacks or drinks between meals is more than 3 times/day" (P = 0.033) and the use of fluoridated toothpaste (P = 0.020). The experimental group was better than the control group in reported oral health behaviors, including frequency of eating sweets before sleep (P = 0.032), brushing time (P = 0.001), and the filled rate (proportion of FS in DMFS) of first permanent molars (P = 0.003).ConclusionsThe online caries management platform showed more advantages than traditional lecturing in improving oral health knowledge and behaviors (oral hygiene practice, sugar consumption behavior, and medical treatment behavior). This platform provides a reliable implementation path for the occurrence and continuous improvement of oral health-related behaviors.